AN ANALYSIS OF THE WRITING ABILITY OF GRADE 11 STUDENTS AT SMAN 3 ACEH BARAT DAYA - Suci Hastuti; Sukri Adani (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the English descriptive text writing ability of grade XI students at SMAN 3 Aceh Barat Daya and identify the factors that cause their low scores. Using a descriptive quantitative approach and supported by qualitative data through interviews, this study evaluated five aspects of writing according to Heaton's theory, namely: content, organization, grammar, vocabulary, and mechanics. Data were collected through descriptive text writing tests and interviews with ten students who had the lowest scores. The results showed that most students had not mastered the structure and linguistic elements in descriptive text. The main problems found include grammatical errors, lack of relevant vocabulary, and irregularity in the organization of ideas. In addition, interviews revealed five main causes of low writing ability: limited mastery of grammar and vocabulary, lack of writing practice, low motivation and confidence, unsupportive learning methods, and lack of access to writing assistive technology. This study recommends the implementation of Contextual Teaching and Learning, the use of assistive technology, and the provision of formative feedback to improve students' writing skills. In addition, continuous writing practice programs and collaboration through peer review are also considered effective for building writing skills.